Some properties of the kernel and the cokernel of Toeplitz operators with matrix symbols - Benhida, B. (2010)
The relations between the kernels, as well as the cokernels, of Toeplitz operators are studied in connection with certain relations between their symbols. These results are used to obtain some Fredholm type properties for operators with 2 x 2 symbols, whose determinant admits a bounded Wiener-Hopf factorization